Program Design Principles to Support Teen-Adult Community Conservation Efforts - Cisneros, Laura M.; Simmons, Jonathan; Campbell, Todd; Freidenfelds, Nicole; Arnold, Chester; Chadwick, Cary; Dickson, David; Moss, David; Rodriguez, Laura; Volin, John C. (Frontiers in Education, 2021)
Researchers and practitioners have identified numerous outcomes of place-based environmental action (PBEA) programs at both individual and community levels (e.g., promoting positive youth development, fostering science identity, building social capital, and contributing to environmental quality improvement). In many cases, the primary audience of PBEA programs are youth, with less attention given to lifelong learners or intergenerational (e.g., youth and adult) partnerships. However, there is a need for PBEA programs for lifelong learners as local conservation decisions in the United States are often carried out by volunteer boards and commissions, which often have little formal conservation training. Intergenerational PBEA programs can provide an opportunity to bring together—in the case of this study—the unique skills and knowledge of teens (e.g., tech-savvy) and adults (e.g., knowledgeable of local community issues) that can lead to innovative ways of addressing real world endeavors that are relevant to participants and their communities. This study describes a program model that offers structured learning opportunities that support intergenerational partnerships (teens and adults) as they contribute to community conservation efforts. We used a design-based research approach to develop and refine program design principles and communication pillars for the purpose of supporting successful teen-adult conservation projects, positive participant experiences, and science identity authoring. The principles and pillars drew on identity, cultural learning pathways, and community conservation research literature as well as previously collected participant interview data from our intergenerational PBEA program. We outline four design principles and four communication pillars that are critical to facilitate collaborative teen-adult environmental action efforts and serve dual functions of providing program guidance and participant support. The aim of these principles and pillars are to establish collaborative team partnership norms that resist traditional hierarchical teen-adult relationships. Further, the principles and pillars consider how partners can draw on their interests, experiences, and knowledge of community, and utilize these assets along with conservation science disciplinary practices to accomplish meaningful science pursuits; thus facilitating how they identify themselves as contributing to science endeavors. Exemplar data and literature that support each principle and pillar are provided, and future extensions of these principles are discussed.